My occupational engagement home program (MYHOeME) / Akehsan Dahlan, Harnisha Haidhir and Tengku Mohd Asri Tengku Makhtar - Dahlan, Akehsan; Haidhir, Harnisha; Tengku Makhtar, Tengku Mohd Asri; Hamid, Nora; Rahim, Nurul Jannah; Abd. Rani, Mohammad Luqman; Krishnan, Thillainathan
In "My Occupational Engagement Home Program," crafted by occupational therapy, we unveil a powerful resource aimed at promoting healthy aging and improving the quality of life for older people. This unique guide is designed to empower the older people to actively participate and engage in their daily routines. Through carefully planned activities and strategies, it fosters independence and a sense of purpose, ensuring that every day is filled with meaningful engagement. But it doesn't stop there—this book also serves as a lifeline for caregivers. By offering practical insights and tailored programs, it alleviates the burden of caregiving, making it easier for loved ones to support the aging process. With a focus on enhancing physical, social, and cognitive well-being, "My Occupational Engagement Home Program" is a comprehensive book that equips older people and their caregivers with the skills and knowledge needed to navigate the aging journey gracefully and joyfully. Discover the transformative power of occupational engagement and embark on a path to healthier, happier aging for you or your loved ones.